Knowledge, attitude and practices regarding dengue in a rural setting of Jammu - Dewan, Deepika; Sahni, Bhavna; Kumar, Dinesh; Bala, Kiran (International Journal Of Community Medicine And Public Health, 2018)
Background: Rapid urbanization, environmental changes and migration of communities is becoming a major reason for increase in number of cases and deaths due to dengue over recent years. Key lies in prevention, since only symptomatic treatment is available. Knowledge, attitude and practice studies provide important information about prevalent scenario regarding awareness of particular health problem in a community. Methods: The present study was descriptive and cross sectional in nature, conducted in July 2017. The study participants belonged to village Tanda of Block RS Pura which is a field practice area of Department of Community Medicine, Government Medical College Jammu. The data was collected by a face to-face interviews of respondents after obtaining informed consent. Enumerators were provided a schedule containing formalized set of questions on knowledge, attitude and practice of dengue control. Information was collected by interviewing the available adult in every second household. Results: Knowledge about dengue was intermediate. Only 35% of the respondents knew atleast two most common symptoms of dengue. They had insufficient knowledge regarding time of dengue mosquito bite and common breeding sites. However attitude of people regarding dengue was good. Almost all the respondents think that dengue is dangerous and one should consult a registered Medical Practioner in case dengue occurs. Commonly used preventive methods included coils and sprays. Drains and surroundings were cleaned to prevent mosquito breeding. Conclusions: There is an urgent need to increase awareness of people especially belonging to rural communities regarding prevention and common signs and symptoms of dengue.